1998
DOI: 10.1177/070674379804300609
|View full text |Cite
|
Sign up to set email alerts
|

What Does Early Antisocial Behaviour Predict? A Follow-up of 4- and 5-Year-Olds from the Ontario Child Health Study

Abstract: The predictive accuracy of antisocial behaviour in 4-and 5-years-old children over 4 years in a nonclinical community population is limited. The clinical, research, and policy implications of this work are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Also, in females, impulsivity and conduct disorder were characterized by running away, self-harming behavior, manipulation, and complicity in committing crimes (essentially theft and fraud), whereas in males it was more likely to characterized by violent behaviors. This is consistent with the empirical literature (Lanctôt & Leblanc, 2002;Lipman, Bennett, Racine, Mazumdar, & Offord, 1998;Salekin, Rogers, & Machin, 2001).…”
Section: Evidence For Gender Differences In the Core Traits And Charasupporting
confidence: 90%
“…Also, in females, impulsivity and conduct disorder were characterized by running away, self-harming behavior, manipulation, and complicity in committing crimes (essentially theft and fraud), whereas in males it was more likely to characterized by violent behaviors. This is consistent with the empirical literature (Lanctôt & Leblanc, 2002;Lipman, Bennett, Racine, Mazumdar, & Offord, 1998;Salekin, Rogers, & Machin, 2001).…”
Section: Evidence For Gender Differences In the Core Traits And Charasupporting
confidence: 90%
“…As described, young children with disruptive behaviour are at risk for a poor outcome. Nevertheless, many children show substantial variability in symptoms over time or desist completely from such externalizing problem behaviours (Lahey et al, 1995;Lipman, Bennett, Racine, Muzumdar, & Offord, 1998;Loeber, 1991;. Focusing on clinical disorders in the Ontario Child Health Study (OHCS), which started in 1983 by collecting information on a province-wide community sample in Canada of more than 3,000 children below 12 years of age, Offord and colleagues (1992) reported that 44% of children diagnosed with CD showed persistent signs of CD at the 4-year follow-up.…”
Section: Problems With Early Identification Based On Childhood-onset mentioning
confidence: 99%
“…A large epidemiologic study of 15-year-olds (n = 1,000) reported that 7.5% to 9.5% of the girls met the DSM-III-R (APA, 1987) criteria for conduct disorders, compared to 8.6% to 12.2% of the boys (Fergusson, Horwood, & Lynskey, 1993). The outcome is reported to be better for boys than for girls with conduct problems (Lipman, Bennett, Racine, Mazumdar, & Offord, 1998). After reviewing the data of a large epidemiologic study, L. N. Robins (1996) determined the following gender distinctions: (a) Boys were younger than girls at first conduct symptoms predictive of adult antisocial behavior, (b) early sexual activity was more predictive of psychopathy for girls than boys, and (c) psychopathy and ASPD in women required a more pathological family background.…”
Section: Conduct Disorders and Adhd As Precursors And Predictors Of Psychopathic And Aspdsmentioning
confidence: 99%